2007
DOI: 10.3923/pjbs.2007.1147.1148
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Sheep Toxoplasmosis in Babol Northern Iran 2004

Abstract: This study is carried-out with the aim of determining the prevalence rate of toxoplasmosis in sheep at Babol (Bandpei part). In this study, 285 sheep of Bandpei area in Babol was selected. The samples studied with indirect immunofluorescence antibody. The results showed that 31.2% of sheep in this study were affected by toxoplasmosis. In positive cases, there was not any statistically significant difference between male and female sheep. The most positive cases observed by 1:200 titer. According to the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Our results were disagreement with Asgari et al (21), who recorded that 22.7% of sheep were infected in southern Iran. Our results were discrepant with those of Akhoundi and Youssefi (22), who explained and related the presence of antibodies to congenital constants in sheep using indirect immunodeficiency technique with the total infection rate of 29.5% Youssefi et al (23) revealed 31.2% infection rate in sheep in Pabol, northern Iran, evidenced a rate of infection in the sheep may range between 17-18% (24), Lazim et al (14) denoted that 26.5% of sheep where infected. Recently, Akhoundi and Youssefi (22) implied that the infection rate was 28.2% in sheep.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results were disagreement with Asgari et al (21), who recorded that 22.7% of sheep were infected in southern Iran. Our results were discrepant with those of Akhoundi and Youssefi (22), who explained and related the presence of antibodies to congenital constants in sheep using indirect immunodeficiency technique with the total infection rate of 29.5% Youssefi et al (23) revealed 31.2% infection rate in sheep in Pabol, northern Iran, evidenced a rate of infection in the sheep may range between 17-18% (24), Lazim et al (14) denoted that 26.5% of sheep where infected. Recently, Akhoundi and Youssefi (22) implied that the infection rate was 28.2% in sheep.…”
Section: Discussioncontrasting
confidence: 99%
“…T. gondii antibodies were detected in the serum samples 50% by using LAT, they concluded that LAT is sensitive test and is efficient for screening purposes Iraqi Journal of Veterinary Sciences, Vol. 35, Supplement I, 2021 (19)(20)(21)(22)(23) Proceedings of the 2nd Scientific Conference, College of Veterinary Medicine, University of Duhok 22 Abouzeid et al (20). Our results were disagreement with Asgari et al (21), who recorded that 22.7% of sheep were infected in southern Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that sheep from southern Kurdistan were at an increased risk of infection to all other regions, possibly associated with its hot and humid environment Higher prevalence rate of toxoplasmosis in warm, moist areas compared to those which are cold and dry is attributed to the longer viability of T. gondii oocysts in moist or humid environments southern Kurdistan is a warm and moist area, which helps T. gondii oocysts to maintain their viability (Van der Puije et al, 2000). The 21.74% seropositivity rate detected in 368 sheep in Kurdistan (West Iran) is lower than those reported by Bonyadian et al (2007), Chegini et al (2002), in center, Sharif et al (2007), Youssefi et al (2007), in North, Hamidinejat et al (2008) in South-West, Hamzavi et al (2007) in west, Asgari et al (2009) in south of Iran,respectively,29.1,25.5,35,31.2,58,22.5,and 26.4%. These differences from different countries indicated that animals bred in these areas were exposed to different environmental contamination with T. gondii Oocysts.…”
Section: Discussionmentioning
confidence: 80%